INTERNALISASI NILAI-NILAI KEISLAMAN DALAM GERAKAN PRAMUKA: KASUS DUA SEKOLAH DI ACEH: INTERNALITATION OF ISLAMIC VALUE IN SCOUT MOVEMENT: THE CASE OF TWO SCHOOL IN ACEH - Afif H M (Penamas, 2014)
This study aims to see how Islamic value internalization performed at the Scout Movement as a vehicle for nurturing young generation. The object of this study is the scout movement in formal educational institutions, Junior High School (SMP) and Islamic Junior Secondary School (MTs). The basic consideration to choose these institutions is that both Junior High School and Islamic Junior Secondary School institutions have different cultures. Data were collected through both in-depth interviews and participant observation. The study found that scout movement has given benefits for the religious education process, primarily concerned with teaching applications in the life of a group. Affective and psychomotor elements of education appeared in the behavior of the scout movement members. Cooperation, mutual respect and admiration are characteristics associated with unanimity of the scout movement members. Besides, scout movement inculcated values of respect differences in a social interaction. Keywords: Islamic education, scout movement, character education, Aceh. Penelitian ini dilakukan untuk melihat bagaimana internalisasi nilai keislaman dilakukan pada Gerakan Pramuka sebagai wahana pembinaan generasi muda bangsa. Sasaran penelitiannya adalah Gerakan Pramuka yang ada di lembaga pendidikan formal, yaitu Sekolah Menengah Pertama (SMP) dan Madrasah Tsanawiyah (MTs). Pertimbangan yang mendasari adalah kedua lembaga pendidikan tersebut memiliki kultur yang berbeda. Data dikumpulkan melalui wawancara mendalam dan observasi terlibat. Hasil penelitian menemukan, bahwa di dua lembaga tersebut Gerakan Pramuka telah memberi nilai tambah (value added) bagi proses pendidikan agama (Islam), terutama adalah menyangkut aplikasi ajaran dalam kehidupan berkelompok. Unsur afektif dan psikomotorik dari pendidikan terjelma dalam perilaku anak-anak yang menjadi anggota Gerakan Pramuka. Kerjasama, saling menghargai, dan menghormati menjadi ciri dari kebersamaan antar anggota pramuka. Di sisi lain, kesediaan untuk menghomati perbedaan menjadi suatu yang ditanamkan dalam interaksi sosial antar anggota Gerakan Pramuka. Kata Kunci: pendidikan agama Islam, Gerakan Pramuka, pendidikan karakter, Aceh.